2017
DOI: 10.31584/smj.2017.35.4.756
|View full text |Cite
|
Sign up to set email alerts
|

Home Visit and Palliative Care

Abstract: To date, an advance in medical technology and science increase the population’s life-span. Hence, palliative medicine, aiming to improve quality of life in patients’ life with incurable diseases becomes essentially significant. Palliative care is a holistic approach, incorporating physical, mental, social and spiritual health. Most Thai patients in the late stage of diseases prefer staying and receiving health care at home where they feel more familiar and restful. In addition, home is the place where they can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Without code Z515, many patients were not able to access to the PC services. [ 37 ] The study of Suvarnabhumi et al . [ 38 ] indicated that the lack of knowledge in PC in medical students in Thailand lowered confidence to practice PC.…”
Section: Discussionmentioning
confidence: 99%
“…Without code Z515, many patients were not able to access to the PC services. [ 37 ] The study of Suvarnabhumi et al . [ 38 ] indicated that the lack of knowledge in PC in medical students in Thailand lowered confidence to practice PC.…”
Section: Discussionmentioning
confidence: 99%